2021
DOI: 10.1002/nop2.1051
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home nurses' turnover intention: A systematic review

Jiyeon Lee

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…Findings of this study identified multiple factors influencing turnover intention among HCWs during the COVID-19 pandemic. The five emerged themes encompassed factors ranging from individual, interpersonal, jobrelated, and organisational determinants, and many of which were known factors prior to the pandemic [11][12][13][14][15][16][17][18][19]. However, the theme 'fear of COVID-19 exposure' was unique and specific to this pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of this study identified multiple factors influencing turnover intention among HCWs during the COVID-19 pandemic. The five emerged themes encompassed factors ranging from individual, interpersonal, jobrelated, and organisational determinants, and many of which were known factors prior to the pandemic [11][12][13][14][15][16][17][18][19]. However, the theme 'fear of COVID-19 exposure' was unique and specific to this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…While some factors are known, turnover is caused by multiple factors, and a fuller understanding of these factors must be pursued if employers seek to reduce turnover. A search for systematic reviews published in the last 10 years examining turnover intention among HCWs on PubMed, PROSPERO and Google Scholar produced nine relevant systematic reviews [11][12][13][14][15][16][17][18][19]; none of which included studies that took place during the COVID-19 pandemic. One integrative review examined the COVID-19 pandemic's impact on predictors of nurses' turnover intention, but it included mainly pre-COVID-19 studies, which diminished the focus of the results regarding the current situation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that improving nurse job satisfaction can reduce nurse turnover and shortages ( 7 , 8 ). Mahoney et al found that nurse job satisfaction among nurse anesthetists in the United States (US) had a direct negative effect on the propensity to leave ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Turnover intention is used to measure employees' intention to resign from their current organization and look for another job [8]. It is con rmed to be the most immediate determinant of actual turnover behaviors and turnover rates [9]. A study conducted in 162 Swiss nursing homes showed that 56% of NAs reported the intention to leave [10].…”
Section: Introductionmentioning
confidence: 99%